2017
DOI: 10.3758/s13414-017-1371-0
|View full text |Cite
|
Sign up to set email alerts
|

What or when? The impact of anticipated social action effects is driven by action-effect compatibility, not delay

Abstract: Motor actions are facilitated if they are foreseeably being imitated rather than counterimitated by social partners. Such beneficial effects of anticipated imitation have been explained in terms of compatibility between one's own actions and their anticipated consequences. Previous demonstrations of these effects might alternatively be explained by consistently faster partner responses for imitative than for nonimitative actions, however. This study contrasts both explanations by using virtual coactors to dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
5
25
0
1
Order By: Relevance
“…Follow-up research has revealed that there are actually two components to the Bbeing imitated^advantage for the model. One component is that the identity of the imitator's response is the same as the model's response (Pfister, Weller, Dignath, & Kunde, 2017). The second component is the time point of the imitator's response-hence, the fact that responses follow quickly because the imitator generates the imitative response more quickly than the counterimitative response (Lelonkiewicz & Gambi, 2016).…”
Section: Anticipation Of Social Action Effectsmentioning
confidence: 99%
“…Follow-up research has revealed that there are actually two components to the Bbeing imitated^advantage for the model. One component is that the identity of the imitator's response is the same as the model's response (Pfister, Weller, Dignath, & Kunde, 2017). The second component is the time point of the imitator's response-hence, the fact that responses follow quickly because the imitator generates the imitative response more quickly than the counterimitative response (Lelonkiewicz & Gambi, 2016).…”
Section: Anticipation Of Social Action Effectsmentioning
confidence: 99%
“…where the followers initiated their responses with constant speed, suggesting that it can be attributed to anticipation of response type rather than response speed (see also Pfister et al, 2017). Note, however, that the relevant statistical effect (i.e., the effect of upcoming response type for trials after compatible responses) was considerably smaller than in Experiment 1 (dz = 0.58 vs. dz = 1.10).…”
Section: Discussionmentioning
confidence: 88%
“…Experiments 2 and 3 used the same task as Experiment 1 but with pre-programmed virtual followers replacing human followers. The main purpose of adopting this design was to allow full control over the timing of responses, while retaining the manipulation of response compatibility (as in Pfister et al, 2017). Specifically, we held the speed with which the followers initiated their responses constant, so we could investigate whether anticipation of the follower's response type affected leaders' actions independently from any phenomena related to response speed.…”
mentioning
confidence: 99%
“…Studies on ideomotor learning through actual practice have demonstrated how action control can be affected by learned associations between actions and a wide range of environmentrelated effects (for reviews see, Hommel, 2013;Shin et al, 2010). Furthermore, consistent with the fact that most actions involve not only consequences in the physical world, but also consequences on the behavior of other people (Kunde et al, 2018), there is accumulating evidence that effect-based action control extends to social action effects (Flach, Press, Badets, & Heyes, 2010;Pfister, Weller, Dignath, & Kunde, 2017). Recent work has also demonstrated how self-performed actions and their affective outcomes become associated, influencing later action control (Eder, Rothermund, de Houwer, & Hommel, 2015;Hommel, Lippelt, Gurbuz, & Pfister, 2017).…”
Section: Discussionmentioning
confidence: 99%